Reassessment of tigecycline bone concentrations in volunteers undergoing elective orthopedic procedures. (24th October 2013) - Bhattacharya, Indranil; Gotfried, Mark H.; Ji, Allena J.; Saunders, James P.; Gourley, Ian; Diehl, Annette; Korth‐Bradley, Joan M.
Abstract The goal of the this study was to re‐evaluate tigecycline bone concentrations in subjects undergoing elective orthopedic surgery, using multiple doses and a more robust bone assay than was used in a previous study. Each subject received three intravenous doses of tigecycline (one 100‐mg infusion followed by two 50‐mg infusions, each administered over 30 minutes). A single bone sample was collected from each subject at one of the following times: 1, 2, 4, 6, 8, or 12 hours after the third dose. Four blood samples were collected from each subject: before the first dose, before and after the third dose, and within 15 minutes of the collection time of the bone sample. Noncompartmental pharmacokinetic analysis serum and bone area under the curve for the given dose interval (AUCτ) values were 2, 402 ng h/mL and 11, 465 ng h/g, and maximum concentration (Cmax) values were 974 ng/mL and 2, 262 ng/g, respectively. The bone to serum ratio calculated using the AUCτ values was 4.77, confirming tigecycline penetration into bone.